1995
DOI: 10.1523/jneurosci.15-04-02972.1995
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde tracing of trigeminal afferent pathways from the murine tooth pulp to cortex using herpes simplex virus type 1

Abstract: Due to its predominantly nociceptive innervation, viral tracing from the tooth pulp provides a potential means for tracing central pain pathways. The neural pathways from the tooth pulp to cortex were determined using in situ hybridization to detect the anterograde transneuronal spread of herpes simplex virus type 1 strain H129 following inoculation into the murine mandibular incisor pulp. Virus first appeared in the brain at day 3 in the dorsomedial region of all three subnuclei of the spinal trigeminal nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 46 publications
(61 reference statements)
6
63
0
1
Order By: Relevance
“…For example, in the present study using H129, we found infection in the ipsilateral DRG beginning at 48 h postinjection, as well as in the ipsilateral T13 sympathetic ganglion. H129 is most useful because of its strictly anterograde travel through neural circuits (6,43,50). The labeling of T13 postganglionic SNS cells may have occurred because they also are first-order neurons, and H129 initially infects all first-order neurons, as was shown with stomach injections of H129 (33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in the present study using H129, we found infection in the ipsilateral DRG beginning at 48 h postinjection, as well as in the ipsilateral T13 sympathetic ganglion. H129 is most useful because of its strictly anterograde travel through neural circuits (6,43,50). The labeling of T13 postganglionic SNS cells may have occurred because they also are first-order neurons, and H129 initially infects all first-order neurons, as was shown with stomach injections of H129 (33).…”
Section: Discussionmentioning
confidence: 94%
“…To this end, we used the H129 strain of the herpes simplex virus-1 (HSV-1), a transneuronal viral tracer that spreads anterogradely (6,17,33,43,50), in contrast to the retrograde of PRV, to trace the multi-synaptic ascending afferent circuit from inguinal WAT (IWAT) or epididymal WAT (EWAT) through the CNS of Siberian hamsters. Immunohistochemical detection of H129 has been previously used in this manner to successfully identify CNS regions that receive viscerosensory inputs from the rat stomach wall (33).…”
mentioning
confidence: 99%
“…The cutaneous small-diameter afferents terminate extensively in the subnucleus caudalis and caudal interpolaris (Gobel et al, 1981;Hayashi, 1985;Jacquin et al, 1988), although there are some data suggesting that some might terminate further rostrally in the VBSNC (Falls, 1988;Sugimoto et al, 1997b; and see Section V). Moreover, primary afferents from the tooth pulp, which is primarily innervated by small-diameter afferents (see Sessle, 1987;Narhi et al, 1994), have been reported in both electrophysiological and anatomical investigations to terminate in great numbers in rostral as well as caudal components of the VBSNC (Tsuru et al, 1989;Hu et al, 1992b;Takemura et al, 1993;Barnett et al, 1995;and see Sessle, 1987).…”
Section: Trigeminal Brainstem Sensory Nuclear Complexmentioning
confidence: 99%
“…1), anterior and dorsal to areas receiving visceral and nociceptive inputs (Cechetto and Saper, 1987;Barnett et al, 1995). The MCA and the RHVs provide anatomical landmarks helping to locate precisely the GC (Yamamoto et al, 1985;Kosar et al, 1986).…”
Section: Functional Localization Of the Gcmentioning
confidence: 99%